Fibre Spring-damper Computational Models in a Laboratory Mechanical System and Validation with Experimental Measurement - Polach, Pavel; Byrtus, Miroslav; Ška, Zbyněk; Hajžman, Michal (Discontinuity, Nonlinearity, and Complexity, 2026)
The paper deals with searching for the phenomenological model of a fibre. A multibody model of a simple weight-fibre-pulley-drive mechanical system is created. This mechanical system is focused on the investigation of a fibre behaviour and experimental laboratory measurements are performed on it. The carbon fibre, which is driven by one drive, is led over a pulley. On its other end there is a prism-shaped steel weight, which moves in a prismatic linkage on an inclined plane. Drive excitation signals can be of different shapes with the possibility of variation of a signal rate. Time histories of the weight position and of the force acting in the fibre are measured. At simulating with the multibody model of this system there is investigated the influence of dependences of the fibre spring-damper coefficients on the velocity of the weight motion in the computational model, on the coincidence of the simulation results and the experimental measurement results are evaluated. The aim of the simulations is to create a phenomenological model of the fibre, which will be utilizable in fibre modelling in the case of more complicated mechanical or mechatronic systems.